Membangun Sikap Bela Negara Mahasiswa Melalui Pendidikan Pancasila di Perguruan Tinggi - Yayuk Hidayahl; Lisa Retnasari; Risti Aulia Ulfah (Jayapangus Press, 2020)
The purpose of this research is to describe the efforts to build the defense of PGSD students through Pancasila Education in Higher Education. The study was carried out in the Department of PGSD Ahmad Dahlan University, Yogyakarta. This research is qualitative research with data collection in the form of interviews, observations, documentation, and Focus Group Discussion (FGD). Data analysis through data reduction, data presentation, and concluding. The results of the study revealed that students of the Department of PGSD Ahmad Dahlan University, Yogyakarta have the conception that the defense of the country is no longer through taking up arms, but can be through their professionalism. Besides, there are some characteristics of students in defending the country, namely, maximizing time as a student with useful activities, loving Indonesia, having morals, excellent skills, and having a national insight. The findings of this study also revealed that Pancasila education in Higher Education became an addendum in providing a basis for students' understanding of Pancasila as the basis of the state.